2020
DOI: 10.1002/jts.22555
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Unique Impacts of Hope and Resilience on Mental Health and Well‐Being in the Wake of Hurricane Harvey

Abstract: Natural disasters can lead to mental health problems, such as posttraumatic stress disorder (PTSD). Higher levels of loss and/or disruption and prior trauma exposure constitute risk factors for mental illness, whereas protective factors, including hope and resilience, support positive functioning. The present cross-sectional study used structural equation modeling to examine the relative influence of resilience and hope on mental health and well-being 1-3 months after Hurricane Harvey made landfall in August 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 67 publications
2
39
1
Order By: Relevance
“…Also, higher level of hope was found to be related with higher level of flourishing and lower level of fear of happiness (Belen et al, 2019). Additionally, previous research indicated that hope decreased psychological distress, anxiety, and depression (Long et al, 2020;Trzebiński et al, 2020;. For example, increased hope was found to be linked with lower levels of depression and anxiety (Cuijpers et al, 2013;Sadoughi et al, 2017;Snyder et al, 1991).…”
Section: Hope and Optimism As Mediatorsmentioning
confidence: 86%
See 2 more Smart Citations
“…Also, higher level of hope was found to be related with higher level of flourishing and lower level of fear of happiness (Belen et al, 2019). Additionally, previous research indicated that hope decreased psychological distress, anxiety, and depression (Long et al, 2020;Trzebiński et al, 2020;. For example, increased hope was found to be linked with lower levels of depression and anxiety (Cuijpers et al, 2013;Sadoughi et al, 2017;Snyder et al, 1991).…”
Section: Hope and Optimism As Mediatorsmentioning
confidence: 86%
“…During the pandemic, individuals' lives extensively interrupted as everyday interactions were replaced by long periods of isolation and loneliness (Armigate & Nellums, 2020;. Additionally, many people experienced a fear of infection and death, anxiety for their loved one's safety, and stress about the uncertainty of the future (Brooks et al, 2020;Gallagher et al, 2020). Further, schools and businesses were suspended, travels restricted, and maintaining social distance was mandated to reduce the spread of the COVID-19 disease (Gostin & Wiley, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is very limited research exploring the relationship between hope and depression during the ongoing COVID-19 pandemic. Hope has also been well established as a factor associated with the process of resilience following exposure to adversities [49][50][51][52]. Notably, prior research showed that hope can be increased through different therapeutic approaches or interventions [53][54][55].…”
Section: The Mediating Role Of Resilience and Hopementioning
confidence: 99%
“…Hope therapy is one of these psychological interventions. Hope is a physiological need of humans that brings them exibility, freshness, and the ability to get rid of life harms and also improves their mental health (20). Considering the effects of hopepromoting group interventions and interaction-induced insight and learning, hope-oriented group counseling can play a major role in improving QoL of patients with incurable and chronic diseases (21).…”
Section: Introductionmentioning
confidence: 99%